Listening to mom in the neonatal intensive care unit: a randomized trial of increased maternal speech exposure on white matter connectivity in infants born preterm - Travis, Katherine E.; Scala, Melissa; Marchman, Virginia A.; Wu, Hua; Dodson, Cory K.; Bruckert, Lisa; Lazarus, Molly F.; Poblaciones, Rocío Velasco; Yeom, Kristen W.; Feldman, Heidi M. (Frontiers in Human Neuroscience, 2025)
ObjectiveEarly speech experiences are presumed to contribute to the development of brain structures involved in processing speech. Previous research has been limited to correlational studies. Here, we conducted a randomized trial with neonates born preterm to determine whether increased exposure to maternal speech during NICU hospitalization is causally linked to structural white matter maturation.Study designWe enrolled 46 neonates born preterm (24–31 weeks gestational age). Participants were randomly assigned to receive increased (T: n = 21) or routine (C: n = 25) exposure to mother’s speech. The T-group heard 10-min audio recordings of their mothers reading a children’s story two times/hour between 10pm and 6am, increasing speech exposure by 2.67 h/day. The C-group did not hear recorded speech. At near-term-equivalent age, we obtained two high-angular resolution diffusion MRI (scan 1: b = 700, scan 2: b = 1500) and T1 relaxometry scans. We assessed mean diffusivity (MD), pre-registered primary outcome (NCT02847689), of the left and right arcuate fasciculus, tracts implicated in language processing. Secondary outcomes included fractional anisotropy (FA) and R1 (1/T1). We hypothesized that neonates randomized to the T-group would show evidence for increased maturation within the arcuate, indexed as decreased MD and increased FA and R1, compared to neonates in the C-group.ResultsGroups were equivalent on medical and demographic variables. Linear mixed models demonstrated that compared to the C-group, the T-group demonstrated significantly lower MD in the left (scan 1: β = −0.11, Marginal R2 = 0.27; scan 2: β = −0.12, Marginal R2 = 0.33) but not right arcuate (scan 1: β = −0.06, Marginal R2 = 0.09; scan 2: β = −0.03, Marginal R2 = 0.01). The T-group also demonstrated significantly higher FA (scan 1 β = 0.02, Marginal R2 = 0.20; scan 2: β = 0.03, Marginal R2 = 0.31) and R1 (β = 0.02, Marginal R2 = 0.39) in the left but not right arcuate.ConclusionPreterm neonates with increased maternal speech exposure showed more mature left arcuate microstructure, supporting a causal role of exposure to speech in brain development. Enhancing speech exposure in the NICU may benefit preterm children’s language outcomes.